INVESTIGATION ON COLOR DIFFERENCE OF DYED COTTON FABRICS WITH EXTRACTS FROM Bixa orellana SEEDS THROUGH CIELAB COLOR SPACE - Anh, Nguyen Tuan; Phuong, Thai Ngo Kim; Tien, Huynh Thi Thanh (HUIT Journal of Science, 2024)
Natural dyes extracted from plants are eco-friendly and biodegradable pigments, using for coloring not only food industry but also textile materials but a lot of their mysteries have not been discovered. This work is to investigate the effects of bleaching agents, dye concentration, exhausting time, mordanting sequence, mordant types and mordant contents on the dyeability of cotton fabrics with Bixa orellana (BO) extracts through color difference (DE) obtained from the CIELAB color system. Based on such investigations, the bonding mechanisms between bixin/norbixin in BO extracts and the cellulose of cotton fibers were clarified. The results demonstrated that bleaching agent prevented the absorbance of dyes into fabrics and the dyeability improved better as increasing dye concentration and exhausting time. The mordant agents enhanced the dyeability of cotton samples with BO extracts, which obtained the highest DE values when dyeing and mordanting samples simultaneously. In fact, potassium aluminum sulfate (KAl(SO4)2.12H2O) played a role as an efficient mordant which presented the higher DE value as compared to copper sulfate (CuSO4.5H2O). The color fastness of dyed samples achieved the grade 3 after a washing cycle and their color staining tests to rubbing were better as mordanting before dyeing process.